The Role of Health-Consciousness and De-stress Motivation on Travel Desire and Intention - Andrulienė, Rasuolė; Urbonavičius, Sigitas (Organizations and Markets in Emerging Economies, 2023)
Health-consciousness is an important reason for travelling to resorts that offer health and wellness services. Additionally, during stressful periods, health-consciousness may trigger de-stress motivation, which is another reason to travel to destinations that help exiting from the stressful conditions. The post-pandemic context presents a situation in which health-consciousness, together with de-stress motivation, could play an important role for travelling to nearby resorts, the services of which together with opportunities to socialize could be seen as desired objectives. However, evidence on the impact of de-stress motivation on desire and intention to travel in post-restriction period is scarce, presenting a notable research gap. This gap is addressed with modelling on the basis of goal-directed behaviour that predicts travelling with the consideration of travel desire and travel intentions. This study concentrates on the impact of health-consciousness and de-stress motivation on desire and intention to travel, with the analysis of data collected from 793 respondents in Lithuania. It was found that health-consciousness and de-stress motivation are positively related to each other and have a significant impact on both travel desire and intention.
Keywords: travel motivation; health-consciousness; travel desire; travel intention